Una Revisión al Estado del Arte del Problema de Ruteo de Vehículos: Evolución Histórica Y Métodos De Solución - Rocha Medina, Linda Bibiana; González La Rotta, Elsa Cristina; Orjuela Castro, Javier Arturo (Ingeniería, 2011)
This paper is a literature review of the history, categories, and solution methods of the vehicle routing problem with multiple trips (Multi-trip VRP). It explains the beginning of the concept of VRP and discusses the different variations that have arisen recently. Solution methods, approaches and tendencies to these variations are described with references to further studies